Analytical development and experimental investigation of the casting multi-plate damper (CMPD). (1st January 2022) - Chen, Yiyi; Ye, Dongchen; Zhang, Lei
Highlights: An innovative cast damper with a set of energy-dissipating plates was proposed and investigated. A mechanical model was presented to get the constitutive frame of the cast damper. Mechanical performance of the damper, including hysteretic behavior, deformability, energy dissipation, etc., were analyzed. The adjustable yielding behavior and multi-level yielding (design concepts of the cast damper) were discussed. Abstract: In parallel to efforts of enhancing the seismic performance of structures, this paper emphasizes the potential of applying casting technology into steel dampers in frame structures for seismic energy dissipation. Casting multi-plate damper (CMPD), which composed of a set of energy-dissipating plates, is proposed in this study. Based on the mechanical concept, the behavior of the damper could be adjusted for specific structures by changing the number and dimension of the energy-dissipating plates. Thus, two types of dampers (S1 and S2) with different configurations of energy-dissipating plates were designed and fabricated for comparison. A mechanical model is presented first to get a better understanding of the damper behavior. Then the experimental investigation follows, and it starts with the tensile test on bar samples. All these tensile bar samples were taken from critical locations of the damper so that the full picture of the material property could be obtained. In subsequent hysteretic tests, dampers display reasonably good seismic performance with sufficient deformation and energy dissipation capacity. In the final, the proposed mechanical model is validated by comparing with test results and the corresponding finite element (FE) models.